Evaluation of ABET accreditation path for a representative African undergraduate computer science programme - Greenlaw, Raymond; Mufeti, Kauna (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2022)
As of the beginning of 2022, only four of 54 countries in Africa had programmes accredited by ABET—the widely used international accreditation body for tertiary education programmes in computing, engineering, applied and natural sciences, and engineering technology. This article provides results from an evaluation of a representative non-ABET-accredited African undergraduate computer science programme—the University of Namibia (UNAM) Bachelor of Science (BSc) in Computer Science—in terms of its potential for ABET accreditation. The study evaluates the UNAM programme against ABET’s General Criteria (GC), and also against ABET’s computer science Program Criteria (PrCr), in order to determine the steps UNAM would need to take were it to seek ABET accreditation for the programme. The authors also evaluate the level of difficulty that each of the steps would likely involve. The authors’ evaluation aims to be replicable, so as to provide a potential tool for use by any African higher education entity seeking ABET accreditation for a learning programme.